Beatus manuscripts under the microscope: the Alcobaça Beatus and the Iberian Cistercian tradition revisited. Issue 2 (2nd July 2016) - Miguélez Cavero, Alicia; Melo, Maria João; Miranda, Maria Adelaide; Castro, Rita; Casanova, Conceição
ABSTRACT: The Alcobaça Beatus (Lisbon, National Library, Alc. 247) is one of the few extant unillustrated copies of the eighth-century Commentary on the Apocalypse attributed to the Iberian monk Beatus of Liébana. It has traditionally been considered that this Beatus was produced at the Cistercian Portuguese abbey of Santa Maria de Alcobaça and that its model was the Lorvão Beatus (Lisbon, Arquivo Nacional da Torre do Tombo, Ordem de Cister, Mosteiro de Santa Maria de Lorvão, Liv. 44). This article provides the first in-depth examination of the Alcobaça Beatus, carried out by a multidisciplinary team using combined methods from the natural and human sciences. The technical data provided by the analysis of the decoration, molecular palette and bookbinding support the theory of its production at the scriptorium of the Portuguese monastery of Alcobaça, whereas the analysis of the textual structure and content reveals that the Alcobaça Beatus and the Lorvão Beatus show a different sequence of texts and that the Alcobaça copy contains later notes that evidence its use in the monastic reading practice, especially the liturgical readings of the Divine Office. This set of results turns this manuscript, which had received minimal scholarly attention to date, into a significant case study since it reveals itself as the basis to further investigate the corpus of extant Beatus copies and question the importance of such a work within the Cistercian order, thus provoking new questions within the debate on Cistercians and their identity around the year 1200.